AS "MANIAS ESQUISITAS" DE CASEMIRA: UM ESTUDO SOBRE A PRÁTICA E O JULGAMENTO DO INFANTICÍDIO. (Revista de História Regional, 2007)
This article has the objective of presenting a casestudy about the practice of infanticide, as well as thetreatment given to this practice in the judiciary of PontaGrossa. Making the analysis of the law suits and presentingthe different arguments of witnesses, relatives, doctors andthe judge about the crime and the affective-sexual life of thedefendant.